PENGARUH PENGENDALIAN INTERNAL DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DI UPTD PUSKESMAS LOTU KABUPATEN NIAS UTARA - Zendrato, Nonitehe; Nababan, Donal; Silitonga, Evawani Martalena; Hidayat, Wisnu; Sitorus, Mido Ester J.; Pane, Masdalina (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Employee performance at the Puskesmas is one of the factors that are expected to support the achievement of the goals of the Puskesmas it self. Employee performance is influenced by several factors, one of which is internal control and leadership style as very fundamental in the administration of government to ensure that government goals are achieved effectively and efficiently. In the initial survey, it was seen that internal control and leadership style had not been implemented properly, so it was seen that many employees were often absent, arrived late and returned home early, and the submission of reports was often late. timely submission of reports. The purpose of this study was to determine the effect of internal control and leadership style on the performance of UPTD Lotu Public Health Center employees, North Nias Regency. The research design used in this study was analytic with a cross sectional approach. The population in this study were 96 employees of the Lotu Health Center UPTD with samples taken from the entire population. The data collection method was primary data and secondary data. The data analysis used was test multiple linear regression. The results showed that internal control had a sig-p value of 0.003 < 0.05, leadership style had a sig-p value of 0.003 < 0.005, which means that internal control and leadership style had an effect on performance. The conclusion in this study is that there is an influence of internal control and leadership style on employee performance at the Lotu Health Center UPTD North Nias Regency in 2020 and it is hoped that the Lotu Health Center UPTD Leader will improve and innovate in internal control and good leadership style.